Marine climate indicators in the Adriatic Sea - da Costa, Vladimir Santos; Alessandri, Jacopo; Verri, Giorgia; Mentaschi, Lorenzo; Guerra, Roberta; Pinardi, Nadia (Frontiers in Climate, 2024)
This research seeks to categorize and ascertain the primary marine climatic indicators within the complex Adriatic Sea area. Employing subregional climate downscaling models with resolution on the scale of a few kilometers, incorporating atmospheric, oceanic, and hydrological coupled models, the study scrutinizes historical baseline simulations (from 1992 to 2011) and future projections (from 2031 to 2050) under the RCP8.5 scenario. The chosen climate indicators are related to Sea Surface Temperature (SST), Marine Heat Waves (MHWs), Brunt–Väisälä frequency, Sea Level Rise (SLR), and Ocean Heat Content (OHC). The main results show the positive trend in SST and its correlation to circulation structures. It is noticeable that the historical period reveals a greater trend compared to the projection period, being 0.04°C/year and 0.022°C/year, respectively. The OHC shows the expected positive trend with a maximum increase in the southern Adriatic Gyre. The stability of the water column, as identified by the Brunt–Väisälä frequency values, is decreased in the shallow northern Adriatic due to the river discharge decrease while it is increased in the mid-depth water column of the central and southern regions. The number and amplitude of MHW increases especially if referenced to the historical period and finally the rate of total sea level rise shows a consistent decrease in the projection period due to compensating effects between warming and salting and the changing water budget.